Jumpstart! storymaking [ games and activities for ages 7-12 - Corbett, Pie (Routledge, 2009)
A collection of games and activities to develop the creative process of 'storymaking'. It focuses upon 'storytelling for writing' as well as creating a whole school culture of storytelling, reading